Neutrophil-to-Lymphocyte Ratio Predicts Restenosis After Drug-Coated Balloon Therapy for Femoropopliteal Artery Lesions: A Retrospective Study - Wang, Zhihong; Sheng, Lei; Gu, Hongbin; Yang, Fan; Xie, Huajie; Li, Mingfei (Frontiers in Cardiovascular Medicine, 2022)
Background: Peripheral artery disease (PAD) is a common atherosclerotic vascular disease. The use of drug-coated balloon (DCB) for the treatment of femoropopliteal artery disease has gradually increased. A certain percentage of patients developed target lesion restenosis after DCB treatment of the femoral popliteal artery. The neutrophil-to-lymphocyte ratio (NLR) is closely related to the level of inflammatory activity and has predictive value for atherosclerotic vascular disease. This study aimed to analyze the relationship between NLR and 1-year restenosis after DCB for femoropopliteal artery disease. Methods: Patients with femoropopliteal artery disease who were treated with DCBs at our hospital from May 2016 to December 2020 were retrospectively included. Baseline data during the patient’s first hospital stay and data during follow-up were collected. Demographic data, laboratory test results, lesion examination results, and major adverse events during the follow-up period were collected. Logistic regression was used to analyze the factors associated with restenosis after DCB. Results: A total of 117 patients were included. During 1-year follow-up, 19 cases (16.2%) of restenosis were detected. Five of these patients (4.3% of total included patients) were readmitted for symptomatic ischemia. No deaths or amputations occurred. Logistic univariate and multivariate analysis showed that baseline hs-CRP level (OR=1.10, 95%CI: 1.05–1.34), lesion length (OR=1.04, 95%CI: 1.02–1.27), use of rivaroxaban (OR=1.08, 95%CI: 1.05–1.39), NLR (OR=1.47, 95%CI: 1.13–2.48), LDL-C level (OR=1.25, 95%CI: 1.05–1.52), and diabetes (OR=1.25, 95%CI: 1.05–1.52) =1.18, 95%CI: 1.06–1.66) were predictors of restenosis. Conclusions: Baseline NLR before DCB can predict the risk of restenosis after surgery.